Evaluation of serum selenium levels in patients with multiple warts: a case-control study in the north of Iran - Narges Alizadeh; Rana Rafiei; Abbas Darjani; Hojat Eftekhari; Kaveh Gharaei Nejad; Elahe Rafiei; Meghdad Nasiri (Wolters Kluwer Medknow Publications, 2022)
Background Some micronutrients including selenium (Se) have immunoregulatory effects in the body. Our hypothesis was that decreased serum Se levels could be associated with some degree of immunodeficiency and increased chance of multiple cutaneous warts. Objective To measure serum Se levels in patients with multiple cutaneous warts and healthy participants to verify its inhibitory role in cutaneous warts. Patients and methods A case-control study was conducted on 136 participants: 68 cases with multiple cutaneous warts and 68 age-matched and sex-matched healthy controls. Collected data were age, sex, number, duration, and clinical type of the warts. Blood samples were taken from all participants for the evaluation of serum Se level. Se level was measured with atomic absorption method. Results Median of the Se level was significantly lower in patients with multiple warts compared with healthy controls (P<0.05), but the frequency of Se deficiency was not significantly different in the two groups. There was not any association between Se level and number of warts, but it was significantly lower in palmoplantar warts compared with genital warts. Conclusion A significant decrease in median Se level in patients with multiple warts even without Se deficiency may cause some decline in immune system against papillomaviruses. Lack of Se deficiency in the north of Iran may have led to nonsignificant differences in the frequency of Se deficiency in the two groups.